United Kingdom : Financial Sector Assessment Program-Systemic Stress, and Climate-Related Financial Risks: Implications for Balance Sheet Resilience. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The FSAP started in an important macro-financial phase right after the second Covid wave and a third lockdown. The balance sheet resilience of major institutional sectors was at the center of policy considerations. Against this backdrop, the FSAP analyzed the pandemic's potential "scarring" of banks, insurers, corporates, and households balance sheets, focusing on the interplay of macro-financial/structural conditions and financial vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy